2014
DOI: 10.4067/s0370-41062014000100012
|View full text |Cite
|
Sign up to set email alerts
|

Sífilis congénita precoz: A propósito de 2 casos clínicos

Abstract: CS has significant diagnostic challenges as there is no test for early confirmation, therefore, a high index of suspicion might be key in the treatment and consequent prognosis. Due to the current epidemiology of the condition, it is also important to focus on preventive measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In addition, the clinical manifestations of CS may be similar to those occurring in other infectious diseases that affect newborns, such as sepsis and, more rarely, septic shock [29–32]. Given that, we considered that these deaths may have been caused by CS, although it was not stated in the DC [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the clinical manifestations of CS may be similar to those occurring in other infectious diseases that affect newborns, such as sepsis and, more rarely, septic shock [29–32]. Given that, we considered that these deaths may have been caused by CS, although it was not stated in the DC [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…All studies that analyzed clinical findings in children with early CS showed some shortcoming in the management of care to the pregnant woman, especially when related to tracking, diagnosing, and providing proper treatment to the mothers as soon as possible (8,28,32) . Researches carried out in Chile, Mexico, and England exposed cases of early CS in which the mothers were only reactive to the second test applied to them or during birth (22)(23)(27)(28)32) . These women may have been infected during pregnancy and present high titer levels at the moment of birth, corresponding to an early stage of the infection.…”
Section: Discussionmentioning
confidence: 99%
“…A via de contágio mais importante é a sexual, e deriva de diversas formas clínicas como: sífilis primária, sífilis secundária, sífilis latente precoce e tardia e sífilis terciária. (Cavagnaro et al, 2014). Apresenta cerca de um milhão de casos por ano e é responsável por mais de 300 mil mortes perinatais.…”
Section: Introductionunclassified
“…Estimativas mostram que a doença afeta um milhão de gestantes por ano em todo o mundo, colocando em risco de morte prematura cerca de 200 mil crianças (Rocha et al, 2021). Na América Latina e no Caribe há 3 milhões de casos novos por ano (Cavagnaro et al, 2014). A Organização Mundial de Saúde (OMS) calcula que 12 milhões de pessoas são infectadas a cada ano no mundo e mais de 90% dessas infecções ocorrem em países em desenvolvimento.…”
Section: Introductionunclassified